Against 'ideological neutrality': on the limits of liberal and neoliberal economic and social human rights. Issue 2 (6th December 2020) - Manfredi, Zachary
Abstract: This article intervenes in contemporary debates about the future of economic and social human rights. It analyses neoliberal and mainstream liberal theories and argues that both approaches substantially limit understanding of these rights. The article concludes by discussing some of the challenges facing an alternative, socialist conception of economic and social rights.